Slight difference in the isomeric oximes K206 and K203 makes huge difference for the reactivation of organophosphorus-inhibited AChE: Theoretical and experimental aspects. (25th August 2019) - Polisel, Daniel A.; de Castro, Alexandre A.; Mancini, Daiana T.; da Cunha, Elaine F.F.; França, Tanos C.C.; Ramalho, Teodorico C.; Kuca, Kamil
Abstract: Studies with oximes have been extensively developed to design new reactivators with better efficiency, and greater spectrum of action. In this study, we aimed to analyze the influence of the Carbamoyl group position change in two isomeric oximes, K203 and K206, on the reactivation percentage of Mus musculus Acetylcholinesterase ( Mm AChE), inhibited by different nerve agents. Theoretical calculations were performed to assess the difference for the oxime activity with inhibited AChE-complexes and the factors that govern this difference. Comparing theoretical and experimental data, it is possible to observe that this change between the oximes results in different reactivation percentage for the same nerve agent, due to the different interaction modes and activation energy for the studied systems. Highlights: Two isomeric oximes were investigated to assess and compare their efficiency. In vitro tests were performed to evaluate the reactivation percentage. Theoretical calculations were performed to compare with the in vitro tests. K206 has a greater intermolecular interaction with the acetylcholinesterase site. K203 has a greater stabilization of its transition state by the enzyme.